CHARACTERIZATION OF SYNTHESIZED SILVER NANOPARTICLES USING LEPIDIUM SATIVUM PLANT - Obaidellah, Jilan; Ahmed, Sabah M. (Science Journal of University of Zakho, 2023)
The biosynthesis of Silver Nanoparticles (Ag NPs) was achieved through the utilization of an extract derived from the plant Lepidium Sativum, commonly referred to as Garden cress. The current study was undertaken to examine the impacts of different concentrations of silver nitrate (AgNO3) (0.1, 0.15, 0.2, 0.25, and 0.3) on the properties of silver nanoparticles. A range of analytical techniques were utilized to examine the characteristics of the nanoparticles, encompassing energy dispersive X-ray (EDX), field emission scanning electron microscopy (FESEM), UV-visible spectrophotometry (UV-Vis), X-ray diffraction (XRD), and Fourier-transform infrared spectroscopy (FTIR). The findings demonstrated and suggested that Lepidium Sativum represents a viable choice for the environmentally friendly production of silver nanoparticles. The UV-Vis spectra of the studied silver nanoparticles (Ag NPs) exhibited a significant level of absorption within the wavelength range of 430-460 nm. The most intense absorption peak, observed at 453 nm, was associated with a concentration of 0.25 mol. The examination of the Field Emission Scanning Electron Microscope (FESEM) images has revealed that the concentration of the solution has a substantial impact on the size, morphology, shape, and orientation of the silver nanoparticles (Ag NPs). The Ag NPs exhibit a mostly spherical and semi-spherical form, with an average particle size ranging from 65 to 80 nm. Additionally, the X-ray diffraction (XRD) analysis revealed that the silver nanoparticles (Ag NPs) synthesized exhibit a high level of purity, consisting solely of silver atoms arranged in a face-centered cubic crystalline lattice structure. The particle size, as determined from the (111) peak, falls within the range of 25.31-67.28 nm. The EDX spectrum analysis indicated that the primary chemical constituent present in the samples was silver (Ag). The silver nanoparticles (Ag NPs) produced at different concentrations exhibited a distinct peak in the UV-Vis spectrum, demonstrating significant absorbance above 400 nm in the visible region and minimal absorption in the UV range. The measured energy band gap (Eg) ranged from 2.05 to 2.3 eV. In addition, the Fourier Transform Infrared (FTIR) spectra of silver nanoparticles (Ag NPs) at different concentrations did not exhibit any discernible peak throughout the monitored range. This observation implies that the silver nanoparticles that were produced using cress plant extract had a high level of purity.